Waste heat recovery and electrical power production on vessels by means of TEG arrays attached on the hull below the underwater line - Armenakis, Yiannis; Chatzis, Sotirios P. (My University, 2019)
This paper describes a first approach to a new technology of producing Electrical Power on ships or self-propelled sea vessels in general, by means of large Seebeck module arrays cladding attached to the inner part of the ship's metal plates consisting its hull, below the waterline. The arrays are fed with exhaust gases from the main or Electrical generator engines or ancillary equipment such as the vessel's burners, incinerators etc. The DC power produced is led via bus bars incorporated to the arrays either to suitable DC/AC inverters or to the ship's main DC control and distribution board. The overall beneficial power produced may lead to severe cuts in fossil fuel consumption and at the same time significantly decrease the ecological footprint of maritime transportation. Knowledge and understanding of the basics of the Seebeck effect theory is a pre-requisite for reading this article. The research on this new technology is continued as part of a PhD research by the author and its international patent is pending.
Keywords: Eco Footprint; Exhaust gases; Fossil fuel; Power; Seebeck elements; TEG; Waste heat recovery; Wet metal plates